2010
DOI: 10.5387/fms.56.1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Ischemic Myocardial Injury and Dysfunction by Cardiac Fibroblast-Derived Factor(s)

Abstract: : Fibroblasts, the majority of non -cardiomyocytes in the heart, are known to release several kinds of substances such as cytokines and hormones that affect cell and tissue functions. We hypothesized that undefined substance(s) derived from cardiac fibroblasts may have the potential to protect against ischemic myocardium. To assess our hypothesis, using rats, we investigated : 1) the effect of cardiac fibroblast -conditioned medium (CM) on the viability of hypoxic cardiomyocytes in vitro, 2) the effect of CM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…TGFβ1, in particular, is thought to be sufficient for CF differentiation into myoCFs [1, 66, 67, 69, 70]. This pro-inflammatory, pro-fibrotic environment is initially adaptive as factors secreted from CFs and myoCFs protect the injured myocardium, and while they may lead to temporary cellular hypertrophy, they promote cardiomyocyte survival [2]. TGFβ1, for example, has been shown to decrease cardiomyocyte death when delivered exogenously during the reperfusion stage of an ischemia-reperfusion rat model [67].…”
Section: Cardiac Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…TGFβ1, in particular, is thought to be sufficient for CF differentiation into myoCFs [1, 66, 67, 69, 70]. This pro-inflammatory, pro-fibrotic environment is initially adaptive as factors secreted from CFs and myoCFs protect the injured myocardium, and while they may lead to temporary cellular hypertrophy, they promote cardiomyocyte survival [2]. TGFβ1, for example, has been shown to decrease cardiomyocyte death when delivered exogenously during the reperfusion stage of an ischemia-reperfusion rat model [67].…”
Section: Cardiac Injurymentioning
confidence: 99%
“…TGFβ1, for example, has been shown to decrease cardiomyocyte death when delivered exogenously during the reperfusion stage of an ischemia-reperfusion rat model [67]. Similarly, in vitro and ex vivo Langendoff studies have suggested a role for non-cardiomyocytes, especially CFs, in mitigating cardiomyocyte injury following hypoxia and ischemia-reperfusion exposure via secretion of unknown cardioprotective substance/s [2]. In addition to pro-inflammatory cytokines, myoCFs also secrete Angiotensin II, Endothelin-1, Natriuretic peptides, and VEGF to facilitate the wound healing process [64].…”
Section: Cardiac Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Cardiac fibroblast conditioned medium (FCM) from neonatal rats has been shown to protect cardiac myocytes against hypoxia induced injury in isolated cells and the growth factors in such medium also had a protective effect against ischemia-reperfusion injury. [3] Protein analysis of the neonatal rat FCM has shown that these cells release proinflammatory cytokines, such as transforming growth factor β-1 (TGF-β1), fibroblast growth factor (FGF), interferon-γ (IFN-γ), cytokine-induced neutrophil chemoattractant (CINC-1), macrophage migration inhibitory factor (MIF), vascular endothelial growth factor (VEGF) and tumor necrosis factor, [2] many of which are significantly upregulated after myocardial injury. [4], [5] Neonatal rat fibroblast also release significant amounts of IGF-1, endothelin A and leukemia inhibitory factor proteins, which are some of the proteins responsible for hypertrophy in cardiac myocytes and increased collagen synthesis in fibroblasts due to FCM.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac fibroblast‐conditioned medium was reported to induce cardioprotective effects in hypoxic cardiomyocytes in vitro and in an ex vivo model of global I/R injury. However, the secretory product of cardiac fibroblasts, which induced these effects, remains to be elucidated .…”
Section: Role Of Cardiac Fibroblastsmentioning
confidence: 99%